Matematyka
loverangel
2017-06-23 10:50:04
Rozwiąż nierówności wykładnicze: a. [latex]( frac{1}{4} )^{ x^{2} -2x} extless frac{(0,5)^{x} }{2^{x} * frac{1}{16} } [/latex] b. [latex] frac{5^{x+4} }{25^{x-1} } extgreater (frac{1}{5} )^{ x^{2} } [/latex]
Odpowiedź
Kakarrot
2017-06-23 14:54:27

[latex]a.\ ( frac{1}{4} )^{ x^{2} -2x} extless frac{(0,5)^{x} }{2^{x} * frac{1}{16} } \ (2^{-2})^{x^2-2x} extless frac{(2^{-1})^x}{2^xcdot 2^{-4}}\ 2^{-2x^2+4x} extless frac{2^{-x}}{2^{x-4}}\ 2^{-2x^2+4x} extless 2^{-x-(x-4)}\ 2^{-2x^2+4x} extless 2^{-2x+4}\ -2x^2+4x extless -2x+4\ -2x^2+6x-4 extless 0\ \ Delta = b^2-4ac=6^2-4cdot (-2)cdot (-4)=36-32=4\ x_{1}=frac{-b-sqrt{Delta}}{2a}=frac{-6-2}{2cdot (-2)}=frac{-8}{-4}=2\ x_{2}=frac{-b+sqrt{Delta}}{2a}=frac{-6+2}{2cdot (-2)}=frac{-4}{-4}=1\ \ xin(-infty,1) cup (2,+infty) \ [/latex] [latex]b.\ frac{5^{x+4} }{25^{x-1} } extgreater (frac{1}{5} )^{ x^{2} } \ frac{5^{x+4}}{(5^2)^{x-1}} extgreater (5^{-1})^x^2\ frac{5^{x-4}}{5^{2x-2}} extgreater 5^{-x^2}\ 5^{x-4-(2x-2)} extgreater 5^-{x^2}\ 5^{x-4-2x+2} extgreater 5^{-x^2}\ 5^{-x-2} extgreater 5^{-x^2}\ -x-2 extgreater -x^2\ x^2-x-2 extgreater 0\ Delta=(-1)^2-4cdot 1cdot (-2)=1+8=9\ x_{1}=frac{1-3}{2}=-1\ x_{2}=frac{1+3}{2}=2\ \ xin(-infty,-1)cup (2,+infty)[/latex]

Dodaj swoją odpowiedź